Compiled Dataset of Centroid Moment Tensor Inversion of Transtensional Opening Events in the Reykjanes Peninsula Rift Zone, SW Iceland ... - Büyükakpınar, Pınar; Isken, Marius Paul; Heimann, Sebastian; Dahm, Torsten; Kühn, Daniela; Starke, Juliane; López-Comino, José Ángel; Cesca, Simone; Doubravová, Jana; Gudnason, Egill Árni; Ágústsdóttir, Thorbjörg (GFZ Data Services, 2024)
This dataset contains the waveforms of 83 earthquakes (Mw>2.7) compiled for the publication "Understanding the Seismic Signature of Transtensional Opening in the Reykjanes Peninsula Rift Zone, SW Iceland" by Büyükakpınar et al. 2024. The dataset comprises three seismic networks deployed on the Reykjanes Peninsula (RP): REYKJANET (7E), GFZ - MAGIC (9H) and the IMO Icelandic National Network (SIL). It includes data from 27 stations distributed over the RP, each with a different installation period. In addition, strain rate recordings from a 21 km long Distributed Acoustic Sensing (DAS) fiber-optic cable are included, using a subset of 40 spatially stacked channels downsampled to 100 Hz. The DAS interrogator was operated by GFZ Potsdam as part of the MAGIC HART Rapid Response Action. Each sub-event directory contains manually selected first P-wave arrival times and first motion measurements for the target events. The data are provided in miniSeed format. The 83 event directories in one folder called ...